CENP-A confers a reduction in height on octameric nucleosomes - Miell, Matthew; Guse, Annika (Nature structural & molecular biology, 2013)
Nucleosomes with histone H3 replaced by CENP-A direct kinetochore assembly. CENP-A nucleosomes from human and Drosophila have been reported to have reduced heights as compared to canonical octameric H3 nucleosomes, thus suggesting a unique tetrameric hemisomal composition. We demonstrate that octameric CENP-A nucleosomes assembled in vitro exhibit reduced heights, indicating that they are physically distinct from H3 nucleosomes and negating the need to invoke the presence of hemisomes.